Problems of fertility in sheep following synchronisation of oestrus with intravaginal sponges - Van der Westhuysen, Jan Marais (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1969.